Cation distribution and magnetic characterization of the multiferroic cobalt manganese Co2MnO4 spinel doped with bismuth - Dos Santos, Maria Elenice [UNESP]; Aparecido Ferreira, Rafael [UNESP]; Lisboa Filho, Paulo Noronha [UNESP]; Peña, Octavio (Elsevier, 2013)
The structural and magnetic properties of the cubic spinel oxide Co 2MnO4 (Fd3m space group) doped with different concentrations of bismuth, were investigated by X-ray diffraction and SQUID magnetometry. The Bi3+ ions entering into the CoIII octahedral sites do not alter the effective moment, μeff ∼8.2 μB, whereas both the magnetization M50 kOe at the highest field (50 kOe) and the field-cooled MFC magnetizations increased when increasing the Bi content. The ferrimagnetic character of the parent compound, Co2MnO4, is maintained for all materials although the antiferromagnetic interactions Co2+-Co2+ are affected, resulting in higher values of the Curie-Weiss temperature. Due to the large ionic radius of Bi, octahedra distortions occur as well as valence fluctuations of the Mn ions, giving rise to Jahn-Teller effects and enhancing the exchange interactions. The off-center Bi3+ ion is responsible of non-centrosymmetric charge ordering and should lead to multiferroïsme conditions for the BixCo2-xMnO4 material. © 2012 Elsevier B.V.
Keywords: Ferrimagnetism; Magnetic properties; Multiferroic materials; Valence fluctuations; Antiferro-magnetic interactions; Cation distributions; Charge ordering; Curie-Weiss temperature; Ionic radius; Magnetic characterization; Mn ions; Multiferroics; Non-centrosymmetric; Octahedral sites; Parent compounds; Space Groups; Spinel oxide; SQUID magnetometry; Structural and magnetic properties; Bismuth; Carbon dioxide; Characterization; Cobalt; Ferrimagnetic materials; Ions; Jahn-Teller effect; Magnetization; Manganese; Manganese oxide; X ray diffraction; Cobalt compounds